Obstructive sleep apnea and driving risk: The current Turkish legislation, controversies, and future perspectives - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Motor vehicle accidents (MVA) are one of the leading causes of death and injury in Turkey. Fatality reduction currently targets increasing seat belt use and reducing high-speeding and alcohol usage. However, sleepiness is increasingly recognized as a contributing factor. Sleepiness accounts for up to 20% of MVAs on monotonous roads, especially highways. The most common medical disorder causing sleepiness is obstructive sleep apnea (OSA). Available data suggest that efficient treatment of OSA may reduce MVAs and MVA-related deaths and injuries. Several attempts have intensively been debated during the last decade in order to develop national and international strategies to screen high-risk drivers for sleepiness and OSA. In accordance with the directive of the European Union, the Turkish legislation has recently been revised for regulation of driving license issues for individuals with OSA. There are still many controversies and difficulties in implementation of these rules in practice. A full-night polysomnography (PSG) is recommended, and treatment should be initiated as soon as possible when the OSA diagnosis is confirmed. However, given the limited resources, at-home portable cardiorespiratory sleep monitoring is a reasonable alternative to PSG for appropriately selected patients with high clinical suspicion for OSA, rather than no-PSG, and no treatment. Additional attempts for development of national guidelines for determining the driving risk, development of new screening tools for objective evaluation of sleepiness in drivers with suspected or confirmed OSA, and educating patients about the risks of excessive sleepiness as well as encouraging clinicians to become familiar with relevant laws are urging.
Keywords: Sleep apnea; Driving risk; Legislation